THE IMPLEMENTATION OF MINIMUM WAGE ESTABLISHMENT BASED ON LAW NUMBER 13 OF 2003 CONCERNING MANPOWER - Nona Rizki Nusantara; Dikha Anugrah; Fathanudien Anthon (UNIFIKASI : Jurnal Ilmu Hukum, 2019)
This study aims to analyze the procedure of minimum wage establishment based on Law No. 13 of 2003 concerning Manpower as well as the implementation of minimum wage establishment based on Law No. 13 of 2003 in Kuningan District. The method used in this study was a descriptive analytical method with an empirical juridical approach. The data were collected through interviews and literature study with data collection tool in the form of field notes. The data were then analyzed by applying qualitative analysis technique. As results, it was revealed that the procedure of minimum wage establishment is based on Law No. 13 of 2003 concerning Manpower in which the establishment of minimum wage is directed towards meeting the decent living needs. The minimum wage is established by the Governor after considering the recommendations provided by Provincial Wage Councils and/or District Heads/Mayors. Meanwhile, the components of and the implementation of the phases of achieving the decent living needs are specified and determined with a Ministerial Decision. Briefly, in general, the implementation of minimum wage establishment which is based on Law No. 13 of 2003 in Kuningan District is quite good since the minimum wage establishment is regulated by the Governor with the consideration that the Governor is more aware of the social, economic and employment conditions in West Java.Tujuan penelitian ini adalah untuk mengetahui prosedur penetapan upah minimum berdasarkan Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan serta implementasi penetapan upah minimum berdasarkan Undang-Undang Nomor 13 Tahun 2003 di Kabupaten Kuningan. Metode penelitian yang digunakan adalah metode deskriptif analitis dengan pendekatan yuridis empiris. Teknik pengumpul data yang digunakan dalam penelitian ini adalah wawancara dan studi kepustakaan dengan alat pengumpul data berupa catatan lapangan. Data penelitian dianalisis dengan menggunakan teknik analisis kualitatif. Hasil penelitian menunjukkan bahwa prosedur penetapan upah minimum berdasarkan Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan bahwa upah minimum diarahkan kepada pencapaian kebutuhan hidup layak. Upah minimum ditetapkan oleh Gubernur dengan memperhatikan rekomendasi dari Dewan Pengupahan Provinsi dan/atau Bupati/Walikota. Komponen serta pelaksanaan tahapan pencapaian kebutuhan hidup layak diatur dengan Keputusan Menteri; serta implementasi penetapan upah minimum berdasarkan Undang-Undang Nomor 13 Tahun 2003 di Kabupaten Kuningan secara umum cukup baik sebagaimana penetapan upah minimum ditetapkan oleh Gubernur dengan pertimbangan bahwa Gubernur lebih mengetahui kondisi sosial, ekonomi, dan ketenagakerjaan di Jawa Barat.